Mother-Related Factors Affecting Vaccine Refusal Towards Elementary School Student in Palembang - Mareta Kurnia Desiani (Community Medicine and Education Journal, 2020)
The low coverage of vaccination in Indonesia is partly due to vaccine refusal by mothers towards their children, especially in primary schools. Vaccinations that aim to provide immunity to children against certain diseases are considered unnecessary and have a negative impact. This research was conducted with the aim of exploring factors related to mothers against refusing vaccines in primary school children. Using a descriptive qualitative observational study design, data were collected through in-depth interviews, focus group discussions, and observations of 44 mothers who have elementary school children in Palembang. Data analysis was performed using an interactive model analysis consisting of three stages namely: data reduction, data presentation, and conclusions and verification. The triangulation method is then performed for data validation. Based on the results of data retrieval to 44 informantts, it was found that maternal factors that influence rejection of vaccines in primary school children are sources of knowledge about immunization, religious factors, trust in vaccination, vaccination safety, husband's role, and lack of socialisation of vaccination.